Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/pds.1300
|View full text |Cite
|
Sign up to set email alerts
|

Utilization review of concomitant use of potentially interacting drugs in Thai patients using warfarin therapy

Abstract: About a half of patients receiving warfarin therapy was prescribed concomitant drug(s) that has a high potential of interactions with warfarin. These patients should be closely monitored and counselled to watch for signs and symptoms of bleeding and thrombosis to avoid adverse events associated with drug interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 12 publications
3
23
1
4
Order By: Relevance
“…This finding is consistent with study by Kotirum, et al [20] and other studies from different parts of the world [9,21,26,29-33]. Understanding the severity of the drug interaction is important for practitioners because major type of interaction is more likely to produce negative outcomes which include either ineffectiveness or over anticoagulation and bleeding risk.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with study by Kotirum, et al [20] and other studies from different parts of the world [9,21,26,29-33]. Understanding the severity of the drug interaction is important for practitioners because major type of interaction is more likely to produce negative outcomes which include either ineffectiveness or over anticoagulation and bleeding risk.…”
Section: Discussionsupporting
confidence: 91%
“…Parallel to this study, an interventional study on recognition and management of drug – drug interactions in inpatients at the Cantonal Hospital of Baden, found 567 DDIs in 502 inpatients, of which 419 (74%) were judged to be clinically relevant [19]. Likewise, the prevalence of DDIs in outpatients was reported as high as 84% [20,21]. Higher prevalence of DDIs is expected from inpatients as compared to outpatients as more intensive management protocols are required to manage inpatients.…”
Section: Discussionmentioning
confidence: 82%
“…As polypharmacy is more common nowadays, other medications coadministered with warfarin can become more problematic in maintaining a stable INR in warfarin users (Greenblatt and von Moltke 2005). According to one research, 84% of the patients on warfarin were found to be also taking the medicines that can affect the INR (Kotirum et al 2007). Therefore a more detailed evaluation and sufficient information for drug interaction with warfarin are required for all drugs available in the market.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from different countries have been published reporting a pronounced increase in polypharmacy as patients age, which highlights the need for prescribers and pharmacists to be aware of drug interactions, particularly in elderly (Astrand et al, 2007;Johnell, Klarin, 2007;Kotirum S et al, 2007;Thijs et al, 2006). It has been estimated that patients taking two drugs face a 13% risk of drug interactions, rising to 38% when taking four drugs, and to 82% if seven or more drugs are given simultaneously (Goldberg et al, 1996).…”
Section: Discussionmentioning
confidence: 99%